2016
DOI: 10.1155/2016/5013132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of CAM Use among People Living with HIV and AIDS in Lebanon: Implications for Patient Care

Abstract: This study aimed to assess the prevalence and determinants of Complementary and Alternative Medicine (CAM) use among People Living with HIV and AIDS (PLWHA) in Lebanon and to identify related issues that may affect patient care. A cross-sectional survey design was used to interview 116 PLWHA in Beirut. The questionnaire addressed sociodemographic and disease characteristics as well as CAM use. The main outcome of the study was CAM use since diagnosis. Data analysis included descriptive statistics and logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 63 publications
(92 reference statements)
1
20
0
1
Order By: Relevance
“…In line with findings of previous studies examining the use of CAM among cancer patients, this study showed that 58% of patients did not disclose CAM usage to their treating physicians [ 42 , 62 ]. When asked about the main reasons for not disclosing, patients in this study reported that CAM use does not need to be discussed with the physician.…”
Section: Discussionsupporting
confidence: 90%
“…In line with findings of previous studies examining the use of CAM among cancer patients, this study showed that 58% of patients did not disclose CAM usage to their treating physicians [ 42 , 62 ]. When asked about the main reasons for not disclosing, patients in this study reported that CAM use does not need to be discussed with the physician.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, female gender and higher income (greater than US$250000 per year and higher literacy) [ 49 ] were associated with higher CAM usage. Education was also positively associated with CAM use [ 50 ]. This study reports higher use of CAM with secondary education compared with Primary school education.…”
Section: Discussionmentioning
confidence: 99%
“…About one-third of Lebanese adults (29.87%) were reported to use CAM in 2015, with the most prevalent being CAM products, specifically herbal supplements 7. Higher rates of use were reported among patients with chronic diseases such as infertility (41%),27 lung cancer (41%),28 and HIV and AIDS conditions (46.6%) 29. A common finding to most of the aforementioned studies was the low rate of disclosure to the treating physicians 7 26 28 30–32.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Higher rates of use were reported among patients with chronic diseases such as infertility (41%), 27 lung cancer (41%), 28 and HIV and AIDS conditions (46.6%). 29 A common finding to most of the aforementioned studies was the low rate of disclosure to the treating physicians. 7 26 28 30–32 This raised concerns about CAM safety, efficacy and impact on the patient health, especially when its use is coupled with poor regulatory frameworks.…”
Section: Introductionmentioning
confidence: 99%